The effect of recycled-acrylonitrile-butadiene-styrene (abs) mixing ratio on the tensile strength of acrylonitrile-Butadiene-styrene (abs) polymer - Siti Nur Ain, Md Salleh (2013)
Plastics are widely used in industries because of the characteristic of plastics itself that toughness, high wear resistance, high impact resistance, easily processing and corrosion resistance. More plastics has been used in industries, more waste will produced. However, the lack information about recycled plastics on mechanical properties would be possible for industries to keep the good characteristic of recycled materials and make some industries produce the low qualities of products. Therefore, the main objective of this study to investigate the tensile strength of ABS, in terms of recycled ABS mixing percentage and to find the suitable percentage of recycled of ABS that can mix with virgin ABS by having the highest value of tensile test. The recycled ABS was crushed into the pallet then was mixed with the virgin ABS in certain percentage. The injection molding was used to produce the specimens. Five specimens were needed for this project of each experiment. It followed an ASTM D638 as a standard. The test that used to determine the strength of the specimen is tensile stress. The result showed there is increasing of the tensile strength when recycled ABS mixed virgin ABS at the ratio of 40% recycled with 60 % virgin.